Profile and Factors Influencing Students’ Scientific Literacy - Astin Putri Setyowati; Gunarhadi Gunarhadi; Akhmad Arif Musadad (AIBPM Publisher, 2022)
The study aims to determine students' scientific literacy skills in biological teaching and to describe the factors that influence scientific literacy. The research subjects were high school students of class XI with a sample of 40 students. Students are given a test containing 10 scientific literacy questions in biology material based on indicators developed by Gormally. The results show there are skill categories denoting and analyzing the use of inquiring methods for which scientific knowledge is obtained results of 55.5% and skill categories related to organization, analytical, and interpretation of quantitative and information data of 50%. The average mastery of biological scientific literacy is 52.75% and is in the very low criteria. The factors that influence students' scientific literacy are learning prosses, the enjoyment of science and students' interest in science. The implication of the findings obtained that in order to improve scientific literacy skill, it is necessary to prioritize constructivism learning activities.Â Keywords: biological teaching, constructivism paradigm, enjoyment of science, interest in science, science learning, scientific literacy.